ANALIS ITSM PADA LAYANAN SISKOHAT DENGAN MENGGUNAKAN METODE ITIL - Sri Rahayu; Tata Sutabri (Jurnal Komunikasi, 2024)
This research discusses the analysis of Information Technology-based Smart Kemenag application service management using the ITIL 3 framework. The research was conducted with the aim of increasing satisfaction with Smart Kemenag application services in smart kemenag applications. The method used in this research is descriptive qualitative with data collection techniques through interviews and observation